Enhancing individual and community disaster preparedness: Individuals with disabilities and others with access and functional needs. Issue 2 (April 2018) - Kruger, Judy; Hinton, Cynthia F.; Sinclair, Lisa Bundara; Silverman, Brenda
Abstract: Preparedness planning is essential to minimizing the impact of disasters on communities and individuals. Attention to the needs of people with disabilities is vital as they have additional needs before, during and after a disaster that are specific to the disabling condition. In this Commentary, we emphasize national guidelines on disability inclusion in emergency preparedness. We examine some potential areas of planning and response that need attention as suggested by preparedness data for people with self-reported disabilities (also referred to as access and functional needs) and highlight selected resources (e.g., tools, trainings, and online webinars) to enhance whole community preparedness and disability inclusion efforts. This Commentary intends to bridge the gap between those various facets of preparedness, at all levels of government and among individuals, with the aim of ensuring that the whole community is prepared to adapt, withstand and rapidly recover from disruptions due to disasters.